Soft gamma-ray selected giant radio galaxies: an update. Issue 3 (17th October 2020) - Bassani, L; Ursini, F; Malizia, A; Bruni, G; Panessa, F; Masetti, N; Saviane, I; Monaco, L; Venturi, T; Dallacasa, D; Bazzano, A; Ubertini, P
ABSTRACT: We present an update on the sample of soft gamma-ray selected giant radio galaxies (GRGs) extracted from INTEGRAL/IBIS and Swift /BAT surveys; it includes eight new sources and one candidate object. In the new sample, all but one source display FR II radio morphologies; the only exception is B21144+35B, which is an FR I. The objects belong to both type 1 and type 2 active galactic nucleus (AGN) optical classes and have redshifts in the range 0.06–0.35, while the radio sizes span from 0.7 to 1 Mpc. In this study, we present for the first time two objects that were never discussed as GRGs before and propose a new candidate GRG. We confirm the correlation between the X-ray luminosity and the radio core luminosity found for other soft gamma-ray selected GRGs and expected for AGNs powered by efficient accretion. We also corroborate previous results that indicate that the luminosity of the radio lobes is relatively low compared with the nuclear X-ray emission. This supports the idea that the nucleus of these GRGs is now more powerful than in the past, consistent with a restarting activity scenario.